SENSITIVE AND RAPID HPLC METHOD FOR THE DETERMINATION OF PIOGLITAZONE IN RAT SERUM (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
A sensitive, accurate and rapid high-performance liquid chromatography with UV-visible detection (HPLC-UV) method for the determination of Pioglitazone in rat serum has been developed. Rosiglitazone was used as internal standard. Pioglitazone and Rosiglitazone are extracted from serum using a liquid–liquid extraction procedure using ethyl acetate. Isocratic separation of Pioglitazone and Rosiglitazone is carried out using a reversed-phase phenomenex C18 (250 mm × 4.6 mm, 5µm) column with mobile phase consisting of methanol and 30 mM ammonium acetate buffer (pH adjusted to 5 with ortho-phosphoric acid) in the ratio 60:40 (v/v) and quantified by UV detection at 269 nm. Analytical run time was less than 10 min. Mean recovery was 97.12% for 0.1-10µg/ml concentrations. The assay exhibited good linear relationship. Quantification limit was at 50ng/ml of Pioglitazone and accuracy and precision were over the concentration range of 0.1-10µg/ml. This method can be used for routine clinical monitoring of Pioglitazone.